MENEMUKAN PENGARUH PENERAPAK SAK ENTITAS PRIVAT TERHADAP PENYUSUNAN LAPORAN KEUANGAN KUD TRI KARSA JAYA - Nuha, Gardina Aulin; Yulinartati, Yulinartati (Universitas Muhammadiyah Jember, 2024)
Tri Karsa Jaya Village Unit Cooperative is one of the active cooperatives in Jember Regency. KUD Tri Karsa Jaya annually prepares financial statements guided by SAK ETAP. With the implementation of SAK Private Entity will replace SAK ETAP, KUD Tri Karsa Jaya must also adapt by analyzing the effect of the use of SAK Private Entity. Therefore, the purpose of this study was to analyze the effect of the use of SAK Private Entity on the preparation of financial statements KUD Tri Karsa Jaya. This research is a qualitative descriptive research. The type of data used is primary data through interviews with the Treasurer of KUD Tri Karsa Jaya. While secondary data obtained through SAK ETAP documents, SAK Private Entity and Financial Statements KUD Tri Karsa Jaya. The results of the research analysis concluded that KUD Tri Karsa Jaya only compiled three financial statements, namely the balance sheet, income statement, and Notes to Financial Statements (CALK). KUD Tri Karsa Jaya presents different terms related to the name of the financial statements prepared. In addition, presenting liabilities in the balance sheet without classifying current and non-current liabilities. Whereas according to SAK EP, liabilities are classified as current and non-current. KUD Tri Karsa Jaya prepares Notes to Financial Statements (CALK) but only limited to nominal details of the balance sheet and income statement. Whereas according to SAK EP, CALK must contain some information that needs to be analyzed.